Issue and Challenges Faced by Teachers in Using ICT in Teaching Processes - Marasini , Amrit; Paudel , Srijana (Educational Journal, 2024)
The integration of information and communication technology (ICT) in secondary level education has been increasing rapidly to enhance the teaching and learning processes. However, the implementation of ICT in the classrooms have been facing significant challenges. This study attempts to explore the issues and challenge faced by the teachers in classroom while using the ICT during their teaching and learning activity. Quantitative research design was employed and self-developed five-point Likert scale questionnaire is used as tool to collect the primary data and distributed among selected teachers. Descriptive statistic including mean and standard deviation were applied to analyze the data to access the extend of the challenge. The key findings of this study indicate that the teachers have been facing the multiple challenge and problems to integrated ICT in curriculum during the classroom teaching activity. In addition, the study also found that these challenges are consistent with previous studies. This study also concludes that infrastructure development, technical support, professional training to teacher, administrative support and pedagogical and curriculum alignment are essential to overcome these barriers and ensure effective ICT integration in classroom teaching.